Alpha‐amylase is a human salivary protein with affinity to lipopolysaccharide of Aggregatibacter actinomycetemcomitans. (28th November 2012) - Baik, J.E.; Hong, S.W.; Choi, S.; Jeon, J.H.; Park, O.‐J.; Cho, K.; Seo, D.‐G.; Kum, K.‐Y.; Yun, C.‐H.; Han, S.H.
Summary Aggregatibacter actinomycetemcomitans lipopolysaccharide (Aa.LPS) is a major virulence factor associated with aggressive periodontitis. Although the recognition of Aa.LPS is potentially initiated by salivary proteins in the oral cavity, Aa.LPS‐binding proteins (Aa.LPS‐BPs) in saliva are poorly characterized. The purpose of this study was to capture and identify Aa.LPS‐BPs in human saliva using a LTQ‐Orbitrap hybrid Fourier transform mass spectrometry. Aa.LPS conjugated onto N‐hydroxysuccinimidyl‐Sepharose® 4 Fast Flow beads (Aa.LPS‐beads) activated Toll‐like receptor 4 and produced nitric oxide and Interferon gamma‐inducible protein‐10, implying that the conjugation process did not alter the biological properties of Aa.LPS. Aa.LPS‐BPs were subsequently isolated from the nine human saliva samples from healthy individuals with the Aa.LPS‐beads followed by identification with the mass spectrometry. Aa.LPS‐BPs include α‐amylase, serum albumin, cystatin, lysozyme C, submaxillary gland androgen‐regulated protein 3B, immunoglobulin subunits, polymeric immunoglobulin receptor, deleted in malignant brain tumors 1, prolactin‐inducible protein, lipocalin‐1, and basic salivary proline‐rich protein 2. Specific binding was validated using a pull‐down assay with α‐amylase which was captured at the highest frequency. Alpha‐amylase demonstrated to interfere with the adherence and biofilm formation of A. actinomycetemcomitans. Even heat‐inactivated α‐amylase showed the interference to the same extent. Conclusively, we identified unique Aa.LPS‐BPs that provide useful information to understand bacterial pathogenesis and host innate immunity in the oral cavity.